Role of miRNA in the Transmission of Metabolic Diseases Associated With Paternal Diet-Induced Obesity - Dupont, Charlotte; Kappeler, Laurent; Saget, Sarah; Grandjean, Valérie; Lévy, Rachel (Frontiers in Genetics, 2019)
The concept of DOHaD (Developmental Origins of Health and Diseases) recognizes that an unfavourable maternal environment alters the developmental trajectory of the foetus and can lead to long-term risk of developing chronic non-communicable diseases. More recently, the concept of a paternal transmission (POHaD) has emerged stressing the impact of paternal overweight or obesity on offspring’s health and development. While very few examples of paternal epigenetic inheritance of metabolic disorders have been evidenced in Human, many experimental mouse models based on high fat diet-induced paternal obesity have been developed to breakdown molecular mechanisms involved in the process. Besides DNA methylation and chromatin structure, sperm short non-coding RNAs have been considered as the main epigenetic vector of inheritance of paternally environmentally induced changes. Among them, sperm miRNA are one particular subspecies sensitive to environmental changes whose obesity modifies the profile in sperm. Once delivered into the zygote, these molecules might induce epigenetic modifications in the embryo, leading to consequences for foetus development and offspring physical and metabolic health latter-on. Furthermore, some data also suggest that metabolic pathologies may be intergenerationally or transgenerationally transmitted.